Let's put in order the accounting records and annual accounts of the agrarian processing companies - Mauleón Méndez, Emilio; Genovart Balaguer, Juana Isabel (REVESCO. Revista de Estudios Cooperativos, 2016)
The substantive legislation on which Agricultural Processing Companies is based has some notable gaps with regard to the pertinent accounting system. There are grey areas concerning compulsory accounting records and their legalization, together with the process for drawing up, checking, approving and depositing the annual accounts.Consequently, in this paper, we will look first at the corporate and accounting records for Agricultural Processing Companies, putting forward proposals in the wake of recent legislation on the legalization of generally applied corporate and accounting documents.A critical analysis will also be made of the entire process of drafting, auditing, approving and depositing the annual accounts and other documents that Agricultural Processing Companies must send each year to their respective regional registries. Legal and mercantile registries will be differentiated from administrative ones and, in this last sense, changes will be suggested with regard to the place and objective of the deposit of such documents.After thirty-four years old, the substantive legislation in economic and accounting matters of the SAT is out of step with the current law, so a review is necessary. Recent regional regulations have not been a real breakthrough in this regard. We assert the existence of a gap between the substantive rules of the SAT and general accounting rules on financial statements, which is unsustainable and it needs a quick legislative action to be canceled.
Keywords: social entity; SAT; accounting; accounting records; annual accounts.